Growth characteristics of Tilia tomentosa Moench. from different districts in the regions of Marmara and western black sea in turkey - Yucedag, Cengiz; Özel, Halil Barış; Ayan, Sezgin; Ducci, Fulvio; Isajev, Vasilije V.; Seho, Muhidin (National Library of Serbia, 2019)
Climate change will affect all ecosystem services of green areas in the districts. In many cases, the tree species in parks and districts are suffering from the increasingly warmer and drier summers and newly immigrated pests and diseases. Tilia tomentosa Moench. is considered as an important tree species under climate change for dry and warm conditions in Central and Southeastern Europe countries. This tree species is often used as valued urban tree. In the present study we investigate the growth patterns of T. tomentosa Moench. in relation to their growing conditions in order to evaluate its interactions in urban contexts. All the studied characters varied significantly among the sampled districts. Within each of the regions, number of flowers showed a wide range 72-104 per m2 in Marmara region and 54-124 per m2 in Western Black Sea region. All studied characters, beyond number of flowers, positively correlated with each other. This study revealed that especially fruit length had a strong and positive correlation with altitude and a high negative correlation with temperature. Further researches are required to quantify more growth flower characters of the species from Turkey.
Keywords: Urban Forestry; Turkey; Flower; Climate Change; Tilia Tomentosa; Plant Science; Growth; 11. Sustainability; 15. Life on land